Penggunaan Model Pembelajaran Berbasis Masalah dalam Menelaah Struktur dan Aspek Kebahasaan Teks Cerpen Siswa Kelas IX SMP Negeri 1 Bulango Timur - G. Ina, Finriani; Masie, Sitti Rachmi; Muslimin, Muslimin; Malabar, Sayama; Nuramila, Nuramila (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2025)
This study addresses the problems of how the implementation of a problem-based learning (PBL) model is carried out in analyzing the structure and linguistic aspects of short stories in grade IX at SMPN 1 Bulango Timur, the factors influencing its application, and the solutions to overcome possible obstacles. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that the learning process using the PBL model was conducted according to the planned design and successfully enhanced students’ critical thinking, communication, and collaboration skills. Furthermore, interviews indicated that no significant inhibiting factors emerged, as both teachers and students played active roles in the learning process. Consequently, specific solutions to address obstacles were not required, since the effectiveness of the model was supported by the teachers’ guidance and students’ active participation. In conclusion, this study confirms that the PBL model is effective in analyzing the structure and linguistic aspects of short stories and contributes to fostering innovative learning at SMPN 1 Bulango Timur.This study addresses the problems of how the implementation of a problem-based learning (PBL) model is carried out in analyzing the structure and linguistic aspects of short stories in grade IX at SMPN 1 Bulango Timur, the factors influencing its application, and the solutions to overcome possible obstacles. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that the learning process using the PBL model was conducted according to the planned design and successfully enhanced students’ critical thinking, communication, and collaboration skills. Furthermore, interviews indicated that no significant inhibiting factors emerged, as both teachers and students played active roles in the learning process. Consequently, specific solutions to address obstacles were not required, since the effectiveness of the model was supported by the teachers’ guidance and students’ active participation. In conclusion, this study confirms that the PBL model is effective in analyzing the structure and linguistic aspects of short stories and contributes to fostering innovative learning at SMPN 1 Bulango Timur.